Energy Policy Analysis, Monetary and Fiscal on Inflation Volatility in Indonesia - Srinita, Srinita; Effendi, Kharisya Ayu (International Journal of Energy Economics and Policy, 2021)
This study aims to analyze inflation’s volatility as a combined phenomenon of energy, monetary and fiscal policies in Indonesia. By using secondary data in the form of a quarter-time series from 2011 to 2019. This study uses descriptive and quantitative data analysis techniques with the help of the Eviews 10. The findings are that all variables have a significant effect on inflation volatility in Indonesia except tax revenue. Thus, it is evident that the volatility of inflation in that country is not only influenced by the monetary side in the form of the money supply, interest rates, and the rupiah exchange rate against the US dollar as seen by monetarists, but is also influenced by the fiscal side in the form of government spending, and policy. energy, namely the price of oil and electricity tariffs. Keywords: Energy Policy, Monetary, Fiscal, Inflation JEL Classifications: E31, E42,E60, E62, Q48 DOI: https://doi.org/10.32479/ijeep.10841